Integrating Augmented Reality Via Assembler Studio To Foster Mathematical Creative Thinking In Islamic Elementary Students - Lita Sepriyanti; Wulan Andini; Ahmad Arifuddin (Universitas PGRI Yogyakarta, 2026)
This study aims to develop Augmented Reality (AR)-based learning media using Assembler Studio and to examine its validity, practicality, and effectiveness in improving students’ mathematical creative thinking skills. The research employed the Research and Development (R&D) method using the ADDIE model with a one-group pretest-posttest design. The subjects were 20 fifth-grade students and a teacher at Public Islamic Elementary School Cirebon City, Indonesia. The results showed that the material expert validation scored 72% (valid category) and the media expert validation scored 96% (very valid category). The practicality of the media was indicated by teacher responses of 80% (practical category) and student responses of 93% (very practical category). The effectiveness was demonstrated by an N-gain score of 0.661 (moderate category) and the paired sample t-test result with a significance value of 0.000 < 0.05, proving a significant difference between pre-test and post-test. Therefore, the AR-based media was declared valid, practical, and effective for use in elementary mathematics learning.